2017
DOI: 10.18632/oncotarget.16353
|View full text |Cite
|
Sign up to set email alerts
|

A consensus-hemagglutinin-based vaccine delivered by an attenuated Salmonella mutant protects chickens against heterologous H7N1 influenza virus

Abstract: H7N3 and H7N7 are highly pathogenic avian influenza (HPAI) viruses and have posed a great threat not only for the poultry industry but for the human health as well. H7N9, a low pathogenic avian influenza (LPAI) virus, is also highly pathogenic to humans, and there is a great concern that these H7 subtypes would acquire the ability to spread efficiently between humans, thereby becoming a pandemic threat. A vaccine candidate covering all the three subtypes must, therefore, be an integral part of any pandemic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…A series of attenuated Salmonella vaccines were constructed to encode HA or other antigens for protecting chickens against H7N9 or H7N1 infection (Hyoung et al . ; Kim et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of attenuated Salmonella vaccines were constructed to encode HA or other antigens for protecting chickens against H7N9 or H7N1 infection (Hyoung et al . ; Kim et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…of antigenic peptides/proteins in vivo due to the absence of DAP and arabinose in vivo (Ashraf et al 2011). A series of attenuated Salmonella vaccines were constructed to encode HA or other antigens for protecting chickens against H7N9 or H7N1 infection (Hyoung et al 2017;. The regulated delayed lysis Salmonella has also been used to deliver alpha toxin and NetB toxin of Clostridium perfringens and showed dramatic protection in a necrotic enteric model in chickens (Jiang et al 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The tissue culture infective dose (TCID 50 ) of H7N9 and H9N2 AIVs, cultivated in the allantoic cavities of SPF embryonated eggs, was calculated in Madin Darby Canine Kidney (MDCK) cells, as described previously [29]. The THP-1 (human monocytic leukemia) cell line used for the in vitro mRNA expression studies of HA2 and M2e antigens was cultured in RPMI media with 10% fetal bovine serum (FBS) and antibiotics, penicillin and streptomycin.…”
Section: Virus and Cell Linementioning
confidence: 99%
“…Thus, effective vaccination strategies should be in place which not only induce protective immune responses but concurrently allows easier manipulation and faster production of vaccines, and can provide broader spectrum of protection against the heterologous strains of influenza viruses [ 14 ]. Earlier studies have reported that live attenuated Salmonella -based vaccines carrying various heterologous bacterial or viral antigens elicit efficient protective mucosal and cell mediated immune (CMI) responses [ 15 ]. Salmonella -based vaccination strategy is highly economical and allows for a quick response to novel influenza viruses, as it eliminates the need for specific pathogen free (SPF) embryonated eggs required for the production of conventional influenza vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have constructed an O antigen intact Salmonella -hemagglutinin (HA) consensus (H7N3, H7N7 and H7N9 sequence) based vaccine that conferred significant protection against the lethal heterologous H7N1 infection in chicken model [ 15 ]. The HA is the most abundant integral viral envelope protein and is the major target for generating protective immunity; however, HA is continuously subjected to antigenic variations either through antigenic drift (point mutations) or rapidly through reassortment with another divergent virus (antigenic shift).…”
Section: Introductionmentioning
confidence: 99%